PROFESSIONAL EXAMINATIONS A Department for Students of Accounting. - Chamberlain, Henry T. (The Accounting Review, 1947)
Abstract The article presents questions and answers to the problems, which were prepared by the Board of Examiners of the American Institute of Accountants and were presented as the first half of the C.P.A. examination in accounting practice in November, 1946. The candidates were required to solve both problems. The weights assigned were: problem 1: 30 points; problem 2: 20 points. The time allowed was four and a half hours. A suggested time schedule is given as: Problem 1: 90 minutes; Problem 2: 120 minutes. It has been asked by the president of Novo Kitchen Aids, Inc., manufacturer of home appliances, to review the company's capital, surplus and reserve accounts and to make such proposals for their revision and balance-sheet presentation as good accounting may suggest. (a) Draft a work sheet, and brief notes or adjusting entries which will indicate and explain the changes in form or content you would recommend, and (b) draw up the reserve, capital stock, and surplus sections of the balance-sheet as at April 30, 1946, as they should be presented. In response to this question, the work sheets and balance sheet are given in the article.